2021
DOI: 10.1097/dcr.0000000000002127
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Emergency Department Visits After Colorectal Surgery

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were observational, and 26 of 29 studies were retrospective. All were cohort studies except for 1 cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggest that many emergency department visits after CRS could be prevented. [64][65][66] Our data suggests that Medicaid/ uninsured patients are using the emergency department as substitute for outpatient care, further adding to costs.…”
Section: Discussionmentioning
confidence: 85%